Government and Poverty Alleviation in Ondo State, Nigeria - Ojo, Akinmulegun Sunday (International Journal of Management and Sustainability, 2014)
Poverty is a household name most especially in the Third World Nations. However, it is a plague that affects all people across the globe. Governments at all levels had embarked on policies and measures at different times to eradicate this menace to no effect. Thus, the phenomenon ‘poverty alleviation’ emanated. This paper therefore examined different measures embarked upon by governments in Nigeria in general and Ondo State in particular with special attention on government activities since the inception of Democracy in 1999. Efforts were made to engage in descriptive comparative analysis of the efforts by successive governments in the state, using econometric analysis of simple ratios and percentages. Most importantly, an in-depth examination of the policies of the present day government (the Dr. Olusegun Mimiko-led administration) was carried out. Not only this, the extent to which these measures had affected the lives of common man on the street was also examined. It was thus found out that the present day administration was able to achieve so much in poverty reduction in the state basically as a result of its grass root (house-to-house, door-to-door) policies implementation. The paper therefore recommends that for a government to achieve its set goal of affecting the lives of her people, such people-based (see-and-buy) policies of the present day administration in Ondo state must be the main stream of such an administration. The type of unmonitored delegation; “money-must-pass-hands” policies where governance is maladapted and hide and seek; corruption laden governance prevail in the administration of a state must be totally jettisoned as this aid diversion of public funds, breeds corruption and enhances poverty.